Addressing safety concerns of long-term probiotic use: In vivo evidence from a rat model - Petra Hradicka; Petra Adamkova; Ludovit Lenhardt; Sona Gancarcikova; Silvia Farkasova Iannaccone; Vlasta Demeckova (Journal of Functional Foods, 2023)
The global market for probiotic supplements is continually expanding. However, the certainty of their safety is still a matter of concern. Since multi-strain probiotics are gaining increasing interest in clinical practice, the aim of the presented study was to evaluate the long-term effects of probiotic mixture on healthy Wistar rats with the focus on colon histology, haematology, serum biochemistry, inflammatory cytokine production and faecal microbiota composition. The long-term supplementation resulted in systemic pro-inflammatory response accompanied by increased abundance of bacterial families associated with the promotion of gastrointestinal inflammation. The important indicators of cardiovascular risk were significantly elevated after long-term probiotic treatment. Even though no histopathological lesions were detected in the colon, enlarged lymphoid aggregates and follicles were observed in probiotic-fed rats. Based on our study, commercially available probiotics for human use which are recommended as prophylaxis should be monitored for possible side effect after long-term usage. Our study thus contributes to the increasingly debated proposal of the scientific community which suggests the need to shift the future of probiotic prescription from the current ‘one-size-fits-all’ scheme into a person/condition-tailored approach with defined time of administration.